2022
DOI: 10.1101/2022.04.09.487733
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intrinsically photosensitive retinal ganglion cells evade temporal filtering to encode environmental light intensity

Abstract: The retina encodes environmental light intensity to drive innate physiological responses. The synaptic basis of such coding remains obscure. Intrinsically photosensitive retinal ganglion cells (ipRGCs) are the only retinal output neurons stably encoding intensity. They do so even without their melanopsin photopigment, so specializations in their synaptic drive from bipolar cells (BCs) must also contribute. Here, we shed new light on mechanisms responsible for this unique intensity-coding drive. By ultrastructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…The proportion of input from each of these types was not found to be significantly different between the Pix ON and the ON alpha (T6 P=0.7, T7 P=0.3, T8 P=0.7, T9 P=0.2, two-proportions z-test with Holm-Bonferroni correction). This is also consistent with results from a different EM volume 21 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The proportion of input from each of these types was not found to be significantly different between the Pix ON and the ON alpha (T6 P=0.7, T7 P=0.3, T8 P=0.7, T9 P=0.2, two-proportions z-test with Holm-Bonferroni correction). This is also consistent with results from a different EM volume 21 .…”
Section: Resultssupporting
confidence: 92%
“…The proportion of input from each of these types was not found to be significantly different between the PixON and the ON alpha (T6 P=0.7, T7 P=0.3, T8 P=0.7, T9 P=0.2, two-proportions z-test with Holm-Bonferroni correction). This is also consistent with results from a different EM volume 21 . Although both RGC types received input from a similar complement of BC types, perhaps the PixON and ON alpha RGCs form synapses with distinct subpopulations of cells within the same BC type?…”
Section: Excitatory Synaptic Conductances Drive Surround Suppressionsupporting
confidence: 92%
“…Prior reconstructions in this volume showed that T9 CBCs contact M5 GCs 48 as well as a pair of cell types that resemble M2 GCs. 49 These are divisible into two types termed M2(8) and M2(9) to reflect their differential weighting of inputs from T8 and T9 CBCs. We determined the motifs of all T9 synapses onto three examples of each GC type.…”
Section: Resultsmentioning
confidence: 99%
“…The slowly evolving and persistent responses we observed in the human PFC have similarity to ipRGCs responses. ipRGCs responses in humans ( 25 ), as well as in the mouse ( 12 14 , 56 ), persist throughout the duration of the stimulus and even after light offset, with the poststimulus response duration increasing with light intensity. Thus, the similarity in light-evoked activity in ipRGCs and the human PFC may suggest a contribution of ipRGCs’ light responses to PFC activation.…”
Section: Discussionmentioning
confidence: 99%
“…Bright light also affects decision-making and working memory, two key functions of the prefrontal cortex (PFC) ( 8 11 ). These light-related effects likely depend upon a specialized output channel of the retina dedicated to a stable representation of environmental illumination: that is, a light-intensity (irradiance) signal ( 12 14 ). However, the origin of the specific light-intensity signal acting in the PFC has yet to be identified.…”
mentioning
confidence: 99%